How Government Support Programs Enhance SMEs’ Dynamic Capabilities and Digitalization: An Investigation of Common Facility Center Program - Awan, Ambreen Zaineb; Khurram Shahzad (Journal of Applied Research and Multidisciplinary Studies, 2023)
Amidst the increasing attention from governments and policymakers on small and medium enterprise (SME) support programs, a notable gap exists in the academic literature regarding understanding of the effects of support programs and the process through which SEMs leverage government support to achieve competitiveness in the digital context of industry 4.0. Grounded in the dynamic capability theory, this study sets out to explore the pivotal role of the Common Facility Centre (CFC) support program in catalyzing SMEs' digital transformation, with a specific focus on the mediating influence of firm reconfiguration capabilities. To test hypotheses, the data was collected from 202 user SMEs using a self-administered survey questionnaire, employing a multi-time and multi-source approach. The findings indicate that CFC support program significantly enhances SMEs' digital transformation, and firms’ reconfiguration capability is a strong mediating mechanism for this effect to take place.